Green optimization of glutaraldehyde vapor-based crosslinking on poly(vinyl alcohol)/cellulose acetate electrospun mats for applications as chronic wound dressings - Ferreira, Marta Albertina Fernandes (2020)
In the last years, chronic wounds have become more prevalent, leading to a huge burden on the healthcare and social systems by requiring specialized protection. Indeed, wound dressings capable of assisting in the healing process are in urgent need. To that effect, nanofibrous dressings with a structure resembling the extracellular matrix have been engineered by electrospinning from combinations of poly(vinyl alcohol) (PVA) and cellulose acetate (CA) and optimized to endure physiological media contact and mechanical stress after crosslinking. Mats were prepared at different PVA/CA ratios, 100/0, 90/10 and 80/20 v/v%, at 10 w/v% concentration in acetic acid and water in a 75/25 v/v% proportion and processed via electrospinning. Processing conditions were optimized to obtain uniform, continuous, bead free mats, with a flexible structure. The instant solubilization of the PVA portion of the mat in aqueous media was surpassed via crosslinking. Even though there are many chemical agents available to accomplish such task, glutaraldehyde (GA) is by far the most common due to its efficiency, ease of access and processing, and low cost. Further, in its vapor form, GA has demonstrated reduced or no cytotoxic effects. The amount of GA, crosslinking time, temperature, and drying procedure were optimized to guarantee mechanically resilient mats by means of the greenest methodology possible. Indeed, it was determined that GA vapor at 25% in water could be applied for 7 h at 60 °C, using 6 mL of solution, in a 130 × 120 mm2 mat with optimal results. All traces of GA were then eliminated from the mats in a controlled environment (41% relativehumidity and 19 °C). In the end, it was seen that the mechanical resilience and thermal stability of the mats were improved after the application of the modified, green GA-based crosslinking, revealing the engineered methodology potential for applications in biomedical devices.